The Effect of Local Injections of Bupivacaine Plus Ketamine, Bupivacaine Alone, and Placebo on Reducing Postoperative Anal Fistula Pain: A Randomized Clinical Trial - Alireza Kazemeini; Mojgan Rahimi; Mohammad Sadegh Fazeli; Seyedeh Adeleh Mirjafari; Hamid Ghaderi; Kamal Fani; Mohammad Forozeshfard; Marzieh Matin (The Scientific World Journal)
Background and Objective. This study aimed to compare the effects of different local anesthetic solutions on postoperative pain of anal surgery in adult patients. Method. In this randomized double-blind prospective clinical trial, 60 adult patients (18 to 60 years old) with physical status class I and class II that had been brought to a university hospital operating room for fistula anal surgery with spinal anesthesia were selected. Patients were randomly divided into 4 equal groups according to table of random numbers (created by Random Allocation Software 1). Group 1 received 3 mL of normal saline, group 2, 1 mL of normal saline plus 2 mL of bupivacaine 0.5%, group 3, 1 mL of ketamine plus 2 mL of bupivacaine 0.5%, and group 4, no infiltration. Intensity of pain in patients was measured using visual analogue scale (VAS) at 0 (transfer to ward), 2, 6, 12, and 24 hours after surgery. Time interval to administration of drugs and overall dose of drugs were measured in 4 groups. Results. Mean level of pain was the lowest in group 3 at all occasions with a significant difference, followed by groups 2, 4, and lastly 1 (P<0.001). Furthermore, groups 2 and 3 compared to groups 1 and 4 had the least overall dose of analgesics and requested them the latest, with a significant difference (P<0.05). Conclusion. Local anesthesia (1 mL of ketamine plus 2 mL of bupivacaine 0.5% or 1 mL of normal saline plus 2 mL of bupivacaine 0.5%) combined with spinal anesthesia reduces postoperative pain and leads to greater comfort in recovering patients.